A comparison of the effectiveness of splinting, exercise and electrotherapy in women patients with hallux valgus: A randomized clinical trial. (September 2021) - Külünkoğlu, Bahar Anaforoğlu; Akkubak, Yasemin; Çelik, Derya; Alkan, Afra
Highlights: Conservative treatment methods improves foot function in patients with mild to moderate HV. Splinting was more effective than exercise and electrotherapy in the management of HV. A combination of splinting, exercise and electrotherapy may be more beneficial to improve HV symptoms. Abstract: Background: Hallux valgus (HV) is a very common foot deformity involving lateral deviation of the hallux and medial deviation of the first metatarsal head. Objectives: To investigate the effects of HV night splinting, exercise and electrotherapy on the HV angle, and foot-specific health-related quality of life. Methods: Sixty women (120 feet) with bilateral HV deformity were randomly assigned to one of three groups — an HV night splint (SP) group, an exercise (EX) group, and a high-voltage galvanic stimulation (HVPGS) (EL) group. The patients in SP group used the HV night splints while resting or sleeping for at least 8 h a day and the patients in the EX group performed exercises 3–4 times a day with 10 repetitions for the duration of the one-month treatment period. Twenty-minute HVPGS was applied in total over three weekly sessions for four weeks in EL group. Angular degrees (hallux interphalangeal angle (HIPA), HV angle (HVA), and intermetatarsal angle (IMA)) were determined before (t0) and three months after treatment (t2). Foot-specific quality of life was assessed using the Manchester-Oxford Foot Questionnaire (MOFQ) at t0, after one month (t1), and at t2. Results: All groups exhibited significant changes in the HIPA, HVA, and IMA angles and outcome measures (p ≤ 0.001). Decreases in the HIPA and IMA angles, and MOFQ-Pain subscale scores, were higher in the SP group than in the other two groups (p < 0.05). IMA angle at t2, MOFQ-Walking score at t1 and t2 and MOFQ-Pain subscale score at t1 were lower in the SP group (p < 0.05). Conclusion: The SP group exhibited more positive effects in the parameters measured than the other two groups. A combination of these conservative treatment approaches may be more beneficial to improve HV symptoms with longer follow-up periods. ClinicalTrials.gov Identifier: NCT04393545.